Integrated Marriage Itsbat: Analyzing The Polemics Behind Its Implementation - Mustika, Dian; Marlina, Siti (Mazahib, 2019)
The existence of the Integrated Marriage Itsbat in Jambi City has begun since 2015 but in 2018, it was no longer implemented. One of the reasons is because the number of participants was decreasing. However, the trial of Marriage Itsbat in the Religious Court was still held. This study tries to examine its implementation in Jambi City and the problems surround it. This is an empirical legal research which employs the qualitative data collection through interviews and documentation. The study finds that the implementation of this program was loaded with a number of problems. Even in the reality, the final goal of this program, which is to help disadvantaged people to obtain rights to marriage certificates, marriage books, and birth certificates in one service unit, was not fully achieved. The results of this study indicate that there were a number of problems that had arisen, including: the existence of this program creating chances for increasing unregistered marriages; registration of participants without going through KUA leading to missed checks related to the clarity of previous marital status; a constraint in the publishing process of a Marriage Certificate; and lack of socialization. Hence, future programs of integrated marriage itsbat should be able to address the unintended consequences.Keywords: Integrated Marriage Itsbat, marriage registration, Religious Court, Compilation of Islamic Law.